The multixenobiotic resistance mechanism in species of invertebrates associated to an urban stream in the Patagonia mountain - Assef, Yanina Andrea (2014)
There are multiple stressors derived from urbanizations that result in frequent disturbances on streams and rivers reducing water quality and threatens aquatic biota. P-glycoprotein (P-gp)-mediated multixenobiotic resistance (MXR) is a defence mechanism analogous to multidrug resistance (MDR), which has been demonstrated in several aquatic organisms. This system protects cells against the entry and the accumulation of xenobiotics and has been proposed as a biomarker for pollution assessment. We conducted a study in a post-urban reach of Esquel stream (Chubut Province) downstream a wastewater treatment plant, in order to assess the presence and activity of MXR in five freshwater macroinvertebrate species (Helobdella michaelseni, Helobdella simplex, Patagoniobdella variabilis, Hyalella curvispina and Chironomus riparius). We measured the accumulation of the model P-gp substrate rhodamine B (RB) in organisms previously exposed to pollution. Our results described the activity of the MXR system in the three species of leeches suggesting their suitability as the in vivo biomonitoring. We also identified a dependence of the transporter activity with the development stage in H. simplex, highlighting the importance of using organisms of similar size classes since it may affect observed results. Finally, we concluded that benthic freshwater macroinvertebrates possess different species-specific levels of MXR activity possibly influencing their natural distribution as well as their survival.